Sistem Informasi Pengelolaan Sampah berbasis Android - Endang Setyawati; Adhi Wibowo; Ekanti Wahyu Riyana (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2019)
N’berkah waste management at Klahang Sokaraja is one of the garbage bank located in Purwokerto. The systemic in this garbage bank is the customer must deposit the waste and then the admin records it in each customer’s saving book. The waste bank service process itself still doesn’t use computer technology and still using reports for its information. That is why customers often lose their passbooks and these passbooks are sometimes broken, so the admin has to check and record back the numbers contained in the passbook. This condition causes data of the reports are not accurate. Which is why a Waste Management Information System is needed. The method used to build this information system is the prototype method. The steps of the prototype method are gathering requirements, designing, coding the system. Hopefully, with the waste management information system, customers can get better information about their contributions to waste management.